Fatwa of Dar al-Ifta’ al-Mishry and Dairah al-Ifta’ al-’Am al-Urduniyyah on Childfree in Marriage - Farah Abida, Rossana; Rohadatul Aisyah, Nabilah; Tussa'banniya, Nabila; Lailatul Musyafa’ah, Nur (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
Among the purposes of marriage in Islam is to have offspring. However, currently, many married couples do not want to have children in their marriage, which is called childfree. This has sparked debate among scholars, including those from Egypt and Jordan. This article examines the fatwa of the scholars of Egypt’s Dar al-Ifta’ and Jordan’s Da’irah al-Ifta’ al-’Am on the law of childfree. This research employs a normative law approach with a conceptual orientation. Data was collected through a library search of fatwas, books, and journal articles that discuss the childfree. The collected data was analyzed using comparative analysis. The study found that Egypt’s Dar al-Ifta’ states that married couples are allowed to choose not to have children if there are valid syar’i reasons, such as health risks or inability to care for children properly. This decision must be mutually agreed upon by both spouses and serve the best interests of the family, drawing an analogy with the decision on ‘azl (coitus interruptus). In contrast, Jordan’s Da’irah al-Ifta’ al-’Am expressly prohibits child-free decisions, as it is contrary to the purpose of marriage in Islam, especially hifz al-nasl. It is based on the hadith and the Jordanian Personal Status Law, which states that childbearing is one of the primary purposes of marriage. The study recommends raising awareness of this childfree issue through in-depth studies and broader discussions among scholars and the public.